Konsep Dasar Manajemen Bimbingan Dan Konseling Dalam Islam - Arsini, Yenti; Handayani Siregar, Sri; Khairunnisa, Khairunnisa; Sya'bi Abdillah, Rajus (Science and Education Journal (SICEDU), 2023)
Guidance and counseling management has a very important role in supporting individual development and assisting in organizing and managing guidance and counseling activities so that a predetermined goal is achieved. This journal discusses the basic concepts of guidance and counseling management in Islam. Through the discussion in this journal, readers are expected to be able to know and understand the basic concepts of guidance and counseling management in Islam. The article we have written will broaden readers' insight so that readers can better understand the basic concepts of guidance and counseling management. The research regarding this article is based on literature research which is of course valid and factual so it can be used as a source of helpful insight.